Análise da resistência mecânica da pasta de cimento com adição de amidos de fruta de lobeira (Solanum lycocarpum), mandioca (Manihot esculenta) e milho (Zea mays) - Locatelli, Ana Paula Klaus (2022)
The strength of the structure is an essential factor in civil construction, therefore, knowledge of the performance of cement is necessary for making structural projects closer to reality. The use of possible plant additives in civil construction is an important example of sustainable practice due to its simplicity of production and abundance in nature. The main objective of this work is to carry out a behavioral study of the mechanical performance of cement paste specimens, under compression stress, when additives of lobeira, cassava and corn fruit starches are used, at different levels, in order to evaluate a possible use of starch in the manufacture of Portland cement. Cassava and corn starches were purchased in the local market and lobeira fruit starch was extracted in the laboratory. Starches were characterized by Scanning Electron Microscopy (SEM), Infrared Absorption Spectroscopy (FTIR) and by thermal analysis, Thermogravimetry (TG) and Differential Scanning Calorimetry (DSC). For the analysis of the cement pastes, water absorption, moisture content and compressive strength tests were performed at the age of 7 and 28 days, with contents of 0.5%, 0.8% and 1.0%. The extraction of starch from the lobe fruit showed a yield in the order of 5.31%. Regarding the granules by SEM, the average diameter of starch from cassava, corn and lobeira were respectively 15.69 µm, 17.90 µm and 12.69 µm. The analysis of FTIR spectra showed characteristic bands to elongations, bending and deformations consistent with the main specific functional groups of the starch polymer. All samples showed main thermal events characteristic of starch, the mass losses of the three starches occurred in three stages. The thermograms of lobeira, cassava and corn fruit starches exhibit a single endothermic peak (Tp) that indicates a measure of crystalline quality, between temperatures of 61-69°C, the energy peak characteristic of starches. Moisture contents were in the minimum order of 85.86% for samples containing 0.5% of corn starch and the maximum order of 96.58% for samples containing 0.8% of corn starch. On the other hand, water absorption was in the minimum order of 28.32% for samples containing 0.8% of corn starch and the maximum order of 30.31% for samples containing 0.5% of Lobeira starch. As for the compressive strength test, the samples with lobeira and corn fruit starch showed almost no significant change in their strength, regardless of content. The samples with cassava starch additive, on the other hand, had an increase in strength of about 22% compared to the average control strength. Therefore, the use of cassava starch addition, at the levels studied, proved to be a viable alternative for use in the chemical composition of Portland cement.